양송이배지로부터 분리한 Klebsiella michiganensis Jopap-1의 식물생장촉진효과 - 김예슬; 윤민호; Kim, Ye-Seul; Yoon, Min-Ho (Journal of mushrooms, 2018)
An auxin-producing bacterium, Klebsiella michiganensis Jopap-1, was isolated from a button mushroom bed in Buyeo-Gun, Chungcheongnam-Do. The strain Jopap-1 was classified as a novel strain of K. michiganensis based on a chemotaxonomic and phylogenetic analysis. The isolated K. michiganensis Jopap-1 was confirmed to produce indole-3-acetic acid (IAA), which is one of auxin hormones by TLC and HPLC analyses. The maximum concentration of IAA ($96.05mg\;L^{-1}$) was detected in the culture broth incubated in R2A medium containing 0.1% L-tryptophan for 48 h at $35^{°}C$ by HPLC quantity analysis. A negative relationship between IAA production and pH variation was estimated to show that the increase of IAA caused acidic pH in the culture. The effect of the supplement on L-tryptophan (precursor of IAA) production was observed to be highest at 0.1% concentration, but was significantly lowered above a concentration of 0.2%. To investigate the growth-promoting effects on the crops, the culture broth of E. michiganensis Jopap-1 was infected to water cultures and seed pots of mung bean and lettuce. Consequently, the adventitious root induction and root growth of mung bean and lettuce were observed to be 2.1 and 1.8 times higher than those of the control.